2014
DOI: 10.1371/journal.pone.0088605
|View full text |Cite
|
Sign up to set email alerts
|

A Population Survey of the Glucose-6-Phosphate Dehydrogenase (G6PD) 563C>T (Mediterranean) Mutation in Afghanistan

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common inherited enzyme defect and an important problem in areas with Plasmodium vivax infection because of the risk of haemolysis following administration of primaquine to treat the liver forms of the parasite. We undertook a genotypic survey of 713 male individuals across nine provinces of Afghanistan in which malaria is found, four in the north and five in the east. RFLP typing at nucleotide position 563 detected 40 individuals with the Mediterranean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…A comparison between the mutations in Arabs and Asians showed that most of the mutations responsible for the G6PDD shared among the two ethnic groups, which could be due to the long history of admixture among the two ethnic groups. These mutations were also shared with other ethnic groups, for example, the most frequent mutation among Arabs, p.S188F, was also frequently reported in Greece, southern Italy, Spain, Bulgaria, Romania, Turkey, and Israel14151617. We identified the most frequent mutations (p.S188F, p.V68M, p.I48T and p.N126D) and unique mutations (p.N135T, p.S179N, p.R246L, and p.Q307P) circulated among Arabs.…”
Section: Discussionmentioning
confidence: 94%
“…A comparison between the mutations in Arabs and Asians showed that most of the mutations responsible for the G6PDD shared among the two ethnic groups, which could be due to the long history of admixture among the two ethnic groups. These mutations were also shared with other ethnic groups, for example, the most frequent mutation among Arabs, p.S188F, was also frequently reported in Greece, southern Italy, Spain, Bulgaria, Romania, Turkey, and Israel14151617. We identified the most frequent mutations (p.S188F, p.V68M, p.I48T and p.N126D) and unique mutations (p.N135T, p.S179N, p.R246L, and p.Q307P) circulated among Arabs.…”
Section: Discussionmentioning
confidence: 94%
“…G6PD gene sequencing was performed with seven pairs of primers designed to amplify all G6PD coding regions for direct DNA sequencing [17–19]. The two silent polymorphic markers, 1311C>T [20] and IVSXI C93T [21], were assessed by amplification of exon 11 and 12 along with introns 11 and 12, as previously described [19, 22]. DNA sequences were assessed by direct sequencing of the PCR product (Macrogen, Seoul, Korea) and analysed with BioEdit bioinformatics programme [365] using NCBI Reference Sequence X55448.1 as G6PD reference.…”
Section: Methodsmentioning
confidence: 99%
“…If the gold standard treatment includes antirelapse therapy (primaquine), then almost none of Afghanistan's vivax malaria cases are adequately treated because of the absence of G6PD testing. G6PD deficiency is high in certain ethnic groups (up to 10% amongst male ethnic Pashtuns), and about 4% at the population level 25,26. The predominant G6PD genotype is the Mediterranean subtype, which is moderate to severe in the presence of hamolytic factors (e.g., primaquine, dapsone).…”
Section: Diagnosis and Treatment Of Malariamentioning
confidence: 99%